ANALISIS STRATEGI MUTU TERHADAP PRESEPSI KONSUMEN PRODUK KERUPUK KULIT ARIYANTO - Intan Nadyma; Sindi Rustilawati; Wirasena Rukasah; Dewi Lestari; Muhammad Hibar Pangestu; Kharisma Fitri Hapsari; Amadea Selma Agnia Elfath (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the effect of the application of the Input-Process-Output (IPO) model and quality control strategies on consumer perceptions of Ariyanto's Cow Skin Crackers products in Sukabumi City. The approach used includes analysis of the IPO model, quality control tools (Seven Tools) Check Sheet, Stratification and Pareto Diagram, and Importance Performance Analysis (IPA). Data were obtained through interviews, observations and questionnaires to 50 active consumer respondents. The results show that the production process still faces obstacles in the aspects of product filling and packaging, which is evident from the highest defect findings in the form of insufficient contents and leaky packaging. IPA analysis places these two attributes in Quadrant I (top priority for improvement). Meanwhile, the attributes of texture, safety and cleanliness of packaging show high performance and importance, which means they need to be maintained. The conclusion of this study is that quality improvement strategies need to focus on controlling filling and packaging to improve competitiveness and consumer satisfaction in a sustainable manner.